Communism and its collapse - White, Stephen, 1945- (Making of the contemporary world., 2001)
Ranging from the Russian revolution of 1917 to the collapse of Eastern Europe in the 1980s this study examines Communist rule. By focusing primarily on the USSR and Eastern Europe Stephen White covers the major topics and issues affecting these countries, including: * communism as a doctrine * the evolution of Communist rule * the challenges to Soviet authority in Hungary and Yugoslavia * the emerging economic fragility of the 1960s * the complex process of collapse in the 1980s. Any student or scholar of European history will find this an essential addition to their reading list.